GAMBARAN PENGETAHUAN TENTANG KONTRASEPSI PIL KEPADA AKSEPTOR KB PIL DI WILAYAH PUSKESMAS PATRANG KABUPATEN JEMBER - Helen Eka Nadia Sari; Nur Riska Rahmawati; Ai Nur Jannah (Jurnal Kesehatan dr. Soebandi, 2016)
Contraception is an attempt of preventing a pregnancy which is available in temporary or permanent. The oral contraceptive pill/hormonal contraceptive pill are one of the contraceptive devices. It contains hormonal agents and is taken at a single dose of one pill every day. It is readily available at nearby drugstores, thus allowing acceptors to obtain it very easily without necessarily having to consult to their midwives. The objective of this research is to identify the level of knowledge regarding the contraceptive pill device to the acceptors of Contraceptive pill device at the coverage area of Patrang Local Health Center. This research employs descriptive design. The population of this research is the entire mothers registered at Patrang Local Health Center who consume contraceptive pill device during August 2014. The sample of this research is taken using accidental sampling technique, numbering 84 respondents. Data is tabulated using the frequency tabulation and later, presented in the form of percentage figures along with narration. The results of this research reveal that the knowledge of contraceptive pill acceptors at the coverage area of Patrang Local Health Center Jember Regency is as follow: moderate (60,71%), good (27,39%), and poor (11,90%). It is expected that the knowledge regarding the contraceptive pill be mastered by the acceptors in order that to promote more effective use of the pill, respectively